Promoting Rechargeable Batteries Operated at Low Temperature - Dong, Xiaoli; Wang, Yong-Gang; Xia, Yongyao (Accounts of chemical research, 2021)
Conspectus Building rechargeable batteries for subzero temperature application is highly demanding for various specific applications including electric vehicles, grid energy storage, defense/space/subsea explorations, and so forth. Commercialized nonaqueous lithium ion batteries generally adapt to a temperature above −20 °C, which cannot well meet the requirements under colder conditions. Certain improvements have been achieved with nascent materials and electrolyte systems but have mainly been restrained to discharge and within a small rate at temperatures above −40 °C. Moreover, the recharging process of batteries based on the graphite anode still faces huge challenges from the simultaneous Li+ intercalation and potential Li stripping at subzero temperatures. Revealing the temperature-dependent evolution of physicochemical and electrochemical properties will greatly benefit our understanding of the limiting factors at low temperature, which is of significant importance. Herein, we dissect the ion movements in the liquid electrolyte and solid electrode as well as their interphase to analyze the temperature effect on Li+-diffusion behavior during charging/discharging processes. An electrolyte is the vital factor, and its ionic conductivity guarantees the smooth operation of the battery. However, it is the sluggish diffusion in the solid, especially the charge transfer at the solid electrolyte/electrode interfaces (SEI), that greatly limits the kinetics at low temperature. Many strategies have been put forward to tame electrolytes for low-temperature application. From a macroscopic point of view, multiple solvents are mixed to adjust the liquid temperature range and viscosity. With respect to the microscopic nature, research is focusing on the solvation structure by formulating the ratio of Li+ ions to solvent molecules. The binding energy of the Li+–solvent complex is crucial for the desolvation process at low temperature, which is manipulated with fluorinated solvents or other weakly solvating electrolytes. On the basis of an optimized electrolyte, electrodes and their reaction mechanism need to be coupled carefully because different materials show totally different responses to temperature change. To avoid the sluggish desolvation process or slow diffusion in the bulk intercalation compounds, several kinds of materials are summarized for low temperature use. The intercalation pseudocapacitive behavior can compensate for the kinetics to some extent, and a metal anode is a good candidate for replacing a graphite anode to build high-energy-density batteries at subzero temperature. It is also a wise choice to develop nascent battery chemistry based on the co-intercalation of solvent molecules into electrodes. Furthermore, the interfacial resistance contributes a lot at low temperature, which need be modified to accelerate the Li+ diffusion across the film. This will be linked to the electrolyte, exactly speaking, the solvation structure, to regulate the organic and inorganic components as well as the structure. Although it is difficult to investigate SEI on a graphite anode owing to its poor performance at low temperature, great efforts on Li metal anodes have offered some valuable information as reference. It is worth mentioning that the improvement in low-temperature performance calls for not only a change in the single composition but also the synergetic effect of each part in the whole battery. The elementary studies covered in this account could be taken as insight into some key strategies that help advance the low-temperature battery chemistry.